Technická závada ano či ne? Nehoda Maserati Quattroporte - Tylšar, Vladimír (Vysoké učení technické v Brně, Ústav soudního inženýrství, 2012)
Jako příčinu dopravní nehody často řidiči havarovaných vozidel uplatňují technickou závadu. Často je však nehoda způsobena nesprávným způsobem jízdy, zejména nepřiměřenou rychlostí. K tomuto dochází častěji v případech, kdy jde o vozidla vysoce výkonná či sportovní a řidič nemá s jejich řízením patřičnou zkušenost.

The cause of traffic accident, often reported later by driver, is some kind of malfunction. Often is the accident caused only by style of driving, especially disproportional velocity of the vehicle. It seems to be more frequent when driving very powerfull or „sporting“ vehicle has been provided by a unpractised person, by a driver with no experience in driving such kind of vehicles.
Malfunction yes or no? Traffic accident of maserati quattroporte
Keywords: Maserati; nehoda; závada; rychlost; Maserati; accident; malfunction; velocity